2020
DOI: 10.1136/bmjopen-2019-034786
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of home delivery in Ethiopia: further multivariate decomposition analysis of 2005–2016 Ethiopian Demographic Health Surveys

Abstract: ObjectiveThis study aimed to assess the trends and factors that had contributed to the change in home delivery in Ethiopia over the last decade.Design, setting and analysisA nationally representative repeated cross-sectional survey was conducted using 2005, 2011 and 2016 Ethiopian Demographic and Health Surveys. Multivariate decomposition logistic regression analysis was employed to identify significant factors that have been contributed to the change in home delivery. Level of statistical significance was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
(23 reference statements)
6
15
0
Order By: Relevance
“…This finding was ubiquitously found in all regions, and while strata-specific home birth proportions varied considerably between the least educated women and the countries on average, almost all countries (63 out of 67) presented home birth rates of less than 12.5% among highly educated women. A low educational level has been described as a driver of home birth, as educated women tend to search for hospital-based care, explained by understanding and knowledge about the risk that birth encompasses ( Tiruneh et al, 2020 ). Higher fertility rates among low-educated women put them at higher risk of adverse birth outcomes, in addition to the risk of being attended by non-skilled personnel or TBA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding was ubiquitously found in all regions, and while strata-specific home birth proportions varied considerably between the least educated women and the countries on average, almost all countries (63 out of 67) presented home birth rates of less than 12.5% among highly educated women. A low educational level has been described as a driver of home birth, as educated women tend to search for hospital-based care, explained by understanding and knowledge about the risk that birth encompasses ( Tiruneh et al, 2020 ). Higher fertility rates among low-educated women put them at higher risk of adverse birth outcomes, in addition to the risk of being attended by non-skilled personnel or TBA.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, women with a lower educational level have a higher probability of complications in relation to home birth care not performed by qualified medical personnel or trained midwives, as well as at the hospital level ( Karlsen et al, 2011 ; Tunçalp et al, 2014 ). Moreover, research has shown that a higher education level of the head of the household – which in LMIC tends to be the men – is also associated with a lower likelihood of home birth ( Tiruneh et al, 2020 ; World Health Organization, 2015 ). Although the specific pathways leading from higher maternal education towards improved maternal health are still unclear ( Mensch et al, 2019 ), key global health institutions have modeled the importance of maternal education in achieving good maternal and neonatal health outcomes ( Karlsen et al, 2011 ; Kassebaum et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, institutional delivery attended by skilled health professionals is crucial for the well-being of the mother and newborns through timely management and treatment of attributable factors (8). Despite the importance of institutional delivery, a signi cant number of deliveries in Ethiopia (69%), Tanzania (59%), Indonesia (57.3%), Kenya-2008/2009 (57%), Kenya-2012 coastal region study (26%), and other sub-Saharan Africa countries are still taking place at home in the absence of specialized service to deal with any potential complications that can happen during delivery (3,(11)(12)(13)(14)(15). Therefore, factors associated with institutional deliveries should be identi ed and interventions on scaling up of maternal and child health service utilizations should be strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…The compositional differences (endowments) 'E' and the effects of characteristics, which are the differences in the coefficients or behavioural change 'C' responses for the selected predictor variables, are the two contributing effects in the multivariate decomposition analysis [50]. As a result, the observed variations in multimorbidity may be decomposed additively into characteristics (or endowments) and a coefficient (or effects of features) component [51].…”
Section: Statistical Approachmentioning
confidence: 99%